(untitled) - Skarsaune, Oskar; (1946-...) (U.S.A, 2007)
Jewish Believers in Jesus: The Early Centuries examines the formative first five centuries of Christian history as experienced by individuals who were ethnically Jewish but who professed faith in Jesus Christ as the Messiah. Offering the work of an impressive international team of scholars, this unique study examines the first five centuries of texts thought to have been authored or edited by Jewish Christians, including the Old Testament Pseudepigrapha, the New Testament Apocrypha, and some patristic works. Also considered are statements within patristic literature about Jewish believers and uses of oral traditions from Jewish Christians. Furthermore, the evidence in Jewish, mainly rabbinic, literature is examined, and room is made for a judicious sifting of the archaeological evidence. The final two chapters are devoted to an enlightening synthesis of the material with subsequent conclusions regarding Jewish believers in antiquity.
Keywords: Jewish Christians